STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA PEGAWAI PADA PT. TRANS MUSI PALEMBANG JAYA - Habena, Ahmad Ridhuan; Sattarudin, M. (Jurnal Ilmiah Administrasi Dan Sosial, 2023)
Based on the author's observations at PT. Trans Musi Palembang Jaya shows that employee performance is not optimal. This can be seen from the activities carried out by some civil servants who are not productive, such as employees arriving late to the office and not returning on time, lack of training for staff and other experts, unprofessionalism in serving both employees and the community, there is a tendency for employees to delay work, so the work becomes piled up. to find out and analyze the Human Resource Development Strategy in improving employee performance at PT. Trans Musi Palembang Jaya. The results of research and discussion, the researchers can draw conclusions, among others: Human Resource Development Strategy in improving employee performance at PT. Trans Musi Palembang Jaya, the provision of education and training (DIKLAT) has been carried out, but it has not been maximized because the new employees are permanent employees, while non-permanent employees are not included in the implementation of education and training. In addition, employees who attend education and training only get one opportunity during their tenure, so they have not been able to improve the performance of all employees. This means that the current performance of some employees is still low. The proof is that the tasks assigned to employees cannot be completed in the allotted time.  Development of Human Resources (employees) in order to improve performance is very important. Therefore, the director of PT. Trans Musi Palembang Jaya provides education and training to employees every year, besides that non-permanent employees are included in education and training. In order to improve employee performance, both permanent employees and temporary employees.  Keywords: Human resource development strategy and employee performance